Deepwater disaster horizon (BBC ACTIVE, 2006)
Horizon reveals the untold story of the 87-day battle to kill the Deepwater Horizon oil blowout a mile beneath the waves - a crisis that became America's worst environmental disaster. Engineers and oil men at the heart of the operation talk for the first time about the colossal engineering challenges they faced and how they had to improvise under extreme pressure. They tell of how they used household junk, discarded steel boxes and giant underwater cutting shears to stop the oil - an operation that one insider likens to the rescue of Apollo 13